Digital marketing approaches and their role in fostering healthy eating behaviors: A systematic literature review - Kumar, Pritam; Mastana, Amarjeet Singh; Phonkaew, Sasithorn; Sajampun, Pair (Edelweiss Applied Science and Technology, 2025)
Addressing dietary and nutritional concerns necessitates the promotion of nutritious meals. This article employs the PICOC framework (Population, Intervention, Comparison, Outcome, Context) to formulate research questions that examine the efficacy of various digital marketing strategies in encouraging consumers to choose healthier dietary options. The Scopus database, accessible through a Scopus API key and managed with Publish and Perish software, was utilized for a systematic literature review. A total of 537 records were initially gathered; after screening and applying inclusion criteria, 30 peer-reviewed articles published between 2019 and 2024 were incorporated into the final research. The findings indicate that the most effective strategies include social media marketing, influencer marketing, content marketing, email marketing, targeted advertising, and mobile marketing. Social media platforms such as Instagram, Facebook, and TikTok enhance engagement through visually appealing and dynamic content. Influencer marketing increases purchase intentions by establishing brand reputation and trust. Targeted email campaigns foster customer loyalty and encourage repeat business. Content marketing helps establish authority and generates organic traffic. Focusing on specific health-conscious consumer demographics significantly improves online visibility and sales. Mobile marketing effectively engages younger, technologically adept demographics through app-based campaigns and various educational activities. The study highlights important implications for human well-being: effective digital marketing can reduce the incidence of diet-related diseases, promote healthier eating habits, and enhance overall societal health. From an industry perspective, these strategies offer organizations opportunities to align with consumer health trends, thereby improving brand positioning, increasing market share, and promoting sustainable growth.